Organizing actor Engagement: A platform perspective - Blasco-Arcas, Lorena; Alexander, Matthew; Sörhammar, David; Jonas, Julia M.; Raithel, Sascha; Chen, Tom (Journal of business research, 2020)
Research on engagement has shifted to a systemic, rather than a dyadic, view that considers the engagement of multiple actors in complex business settings. Existing literature suggests that actor engagement in business settings is dependent on, and inextricably linked with, service ecosystems, platforms, and the value co-creation process. However, despite its potential to deliver strong performance for organizations, actor engagement in complex business settings has yet to be examined empirically. To gain a deeper understanding of engagement dynamics in these settings, this qualitative study explores the evolution of actor engagement on a platform. The findings offer three main contributions: (i) a typology of three organizing modes of engagement (orchestrating, facilitating, and stimulating), (ii) an understanding of the modular architecture that supports actor engagement within clearly defined rules of exchange, and (iii) insight into engagement activity over time reveals that actors’ engagement states oscillate between object or subject of engagement.